Frequency Of Work-Related Musculoskeletal Disorders Among Laundry Workers - Suarjana, I Wayan Gede; Negara, Ni Luh Gede Aris Mayta; Palilingan, Richard Andreas (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 10 No 01 (2024): Volume 10 No 01 Tahun 2024, 2024)
Work-related musculoskeletal disorders are a serious problem that can affect the health and productivity of laundry workers. Workers who experience such disorders may experience pain, muscle stiffness, joint inflammation, and even serious injury. This study aimed to investigate the frequency of work-related musculoskeletal disorders among laundry workers in North Sulawesi. This study was a quantitative, descriptive cross-sectional survey conducted over 1 month in the Tondano - Tomohon Region. A total sample of 225 laundry workers was taken using the accidental sampling technique. The questionnaire used was the Nordic Body Map. The chi-square test was applied to analyze the association between age and musculoskeletal disorders among laundry workers. Complaints felt in all parts of the worker's body 5.38% were very pain, 17.81% were pain, 36.39% were rather pain, and 39.67% were not pain. The body part that experienced the most complaints of severe pain was back at 10.2%, feeling pain was the waist at 37.3%, feeling pain was the right arm at 47.1%, and no pain was the left elbow at 71.6%. Frequency of work-related musculoskeletal disorders, specifically back and lumbar pain to severe pain, among laundry workers. An association was found between the age of laundry workers and the frequency of WMSDs. Thus, appropriate interventions need to be taken to improve working conditions, protect workers' health, and minimize the risk of work-related musculoskeletal disorders in the laundry industry.